Collaborative Governance Review on G20’s Global Health Infrastucture Priority Issue – The Indonesia Presidency 2022 - Noor Shaky Iskandar; Retnayu Prasetyanti (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2023)
In 2022, Indonesia will serve as the forum's president. This brings Indonesia to the attention of the global community. Due to restrictions, the COVID-19 pandemic has been plaguing the world for about two years, making it difficult to implement the G20 in Indonesia. Thus, the three main topics of discussion at the 2022 G20 will be: 1) digital transformation; 2) sustainable energy transition; and 3) global health architecture. This paper employs the Collaborative Governance model developed by Ansell & Gash (2008) to examine how the Indonesian G20 Presidency in 2022 collaborates on important global health architecture issues. A review of the literature and internet-based data analysis using the Vos Viewer application comprise the qualitative research methodology. The results of this research are: 1) the relevance of collaborative governance theory to the G20 forum. Seeing how G20 members and participants interact in discussing priority issues of global health architecture. 2) describe the G20 collaboration process using the Ansell & Gash (2008) collaborative governance model. 3) pentahelix as a tool to further emphasize the role of G20 members and participants in the ongoing collaboration process. This research has theoretical implications which prove that collaborative governance can be used to analyze the G20 forum and answer the challenges of the Covid-19 Pandemic.